Indicative Planning of the West Malaysian Economy Using an Input-Output Projection Model - Abd Aziz, Abd Rahman (1985)
This paper discusses an input-output projection model which has been used for indicative planning of the West Malaysian economy into 1985. The model projects the structure of the economy including output, investment and labour in 1985 given a level of aggregate domestic consumption likely to be utilised in the target year. The basic projection indicates that the growth rate in per capita private consumption of4 per cent per annum assumed in the model appears infeasible, particularly £n terms of investment and labour requirements. The advent of technological changes, however, results in substantial reduction in investment, labour and export requirements, thus increasing the propor· tion of consumption in Gross Domestic Product in the target year. An increase in export prices also reduces the level of capital formation, exports and labour required to sustain the projected growth rate in consumption. The analysis of impHcations of an import replacement poHcy shows that import substitution of manufactured goods reduces the strain on the economy. However, import-substitution is benejt'c£al only up to a point where the pn'ce of domestically-produced manufactures is 10 per cent higher than the overseas prices.